Metastatic dissemination with special emphasis on breast cancer cutaneous metastases - Luna, Amalia (2015)
Metastatic development is a complex, multistage process involving modulation of cell phenotype, cell migration, and dynamic homeotypic as well as heterotypic cell-cell interactions. In breast cancer, MUC1 mucin has been emerging as a key molecule involved in metastasis. MUC1 is a large transmembrane glycoprotein expressed by mammary normal epithelial cells but it is overexpressed and underglycosylated in cancer cells. Cutaneous metastasis is a neoplastic lesion localized at the dermis or subcutaneous cellular tissue, which is not contiguous to the primary tumor, with an overall incidence of 5.3%. The most common tumor to metastasize to the skin is breast cancer with an incidence of 24%. We present a minireview on metastatic dissemination with special emphasis on breast cancer cutaneous metastases and the role that MUC1 plays on it.